(untitled) (Italian Journal of Public Health, 2008)
Background: Childhood undernutrition is a major public health problem in developing countries. In view of this, the objective of the present study was to evaluate the rates of stunting, underweight and wasting among 2-6 year old rural children of Bengalee ethnicity. Methods: In this study, 20 Integrated Child Development Services (ICDS) Centres of Bali gram panchayet, Arambag, Hooghly District, West Bengal, India, were selected. A total of 1012 (boys = 498; girls = 514) 2-6 year old children were studied. Height-for-age (HAZ), weight-for-age (WAZ) and weight-for-height (WHZ) < -2 z-scores were used to evaluate stunting, underweight and wasting, respectively, following the National Center for Health Statistics (NCHS) Guidelines. Classification of severity of malnutrition was done based on the World Health Organization recommendations. Results: Boys were significantly heavier than girls at ages 2-4 years; they were significantly taller at ages 2 and 4. Significant age differences existed in mean height and weight in both sexes. Mean HAZ, WAZ and WHZ were less than those of NCHS for both sexes at all ages. The overall (age and sex combined) rates of stunting, underweight and wasting were 26.6 %, 63.3 % and 50.0 %, respectively. The prevalence of stunting (boys = 24.9 %; girls = 28.2 %), and underweight (b = 62.2 %; g = 64.4 %) was higher among girls whereas that of wasting was higher among boys (b = 52.4 %; g = 47.4 %). Based on World Health Organization classification of severity of malnutrition, the overall prevalence of stunting was medium (20 . 29 %), whereas those of underweight (. 30 %) and wasting (. 15 %) were very high, in both sexes. Conclusions: The nutritional status of the subjects was unsatisfactory indicating a major public health problem. There is scope for much improvement in the form of enhanced supplementary nutrition.